2008
DOI: 10.1177/1352458507087844
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of patients with multiple sclerosis from a survey in Shanghai, China

Abstract: Clinical features of patients with MS are described based on the information from the largest case series reported among Chinese. Comparisons and discussions are made with findings from the other populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 17 publications
2
21
0
Order By: Relevance
“…The diagnostic criteria for NMO proposed by Wingerchuk et al [2] facilitate its distinction from MS. However, MS patients with lesions involving the spinal cord and optic nerves are very common in Asian countries, including China [3] , resulting in the difficulty in discriminating it from NMO. Beyond this, early diagnosis is critical for these two diseases, because of their distinct treatment regimens, especially during the first episode, when they are termed 'clinically isolated syndromes' [4] .…”
Section: Introductionmentioning
confidence: 99%
“…The diagnostic criteria for NMO proposed by Wingerchuk et al [2] facilitate its distinction from MS. However, MS patients with lesions involving the spinal cord and optic nerves are very common in Asian countries, including China [3] , resulting in the difficulty in discriminating it from NMO. Beyond this, early diagnosis is critical for these two diseases, because of their distinct treatment regimens, especially during the first episode, when they are termed 'clinically isolated syndromes' [4] .…”
Section: Introductionmentioning
confidence: 99%
“…This has been confirmed in many studies, and the presence of such antibodies is now among the diagnostic criteria for NMO 5,6 .…”
Section: Discussionmentioning
confidence: 59%
“…A specific IgG autoantibody, NMO-IgG, selectively targeting aquaporin 4 (AQP4), which accumulates in the central nervous system (CNS) microvessels, pia, subpia, and Virchow-Robin space, has been confirmed by indirect immunofluorescence with a composite substrate of mouse tissue 3,4 . According to this antibody, the new diagnostic criteria for NMO proposed by Wingerchuk et al facilitate its distinction from multiple sclerosis (MS) 5,6 . In subsequent studies, analysis of pathological brain lesions in NMO patients revealed a pattern of vasculocentric immune complex deposition and AQP4 loss ORIGINAL ARTICLE identical to that seen in NMO lesions, suggesting that AQP4 antibodies are related to NMO pathology 7,8 .…”
mentioning
confidence: 99%
“…Based on limited epidemiologic studies, the prevalence of MS in mainland China is estimated at 1.39/100,000 persons, much lower than in adjacent regions such as Hong Kong, Taiwan, Japan, and South Korea (5-10/100,000). [17][18][19] Although there is no apparent reason for a lower MS presence in mainland China compared with adjacent regions, the actual number of such patients is not fewer given China's large population base. For management of acute relapses, steroids, plasma exchange, and IV immunoglobulin are available.…”
Section: Challenges Facing Practicing Neurolo-gists In Chinamentioning
confidence: 99%